Issues of onion supply in Malaysia / Syaza El Shamimi Shari@Shaari ... [et al.]. - Shari@Shaari, Syaza El Shamimi; Abd Karim, Siti Nursyahira; Sabri, Noor Hidayatul Husna; Ahmad Nazari, Hawa; Ali, Asiah (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2025)
Onions are widely used in Malaysia, with most supplies imported from India, China, Pakistan, and the Netherlands. However, recent disruptions in these supply chains have led to shortages and rising prices. Factors such as climate change, trade restrictions, and global crises have significantly impacted onion production and exportation. Climate Change and Weather Conditions, India, one of Malaysia's top suppliers, experienced heavy rains and floods that destroyed onion crops. Other than that, unstable weather patterns in China and the U.S. affected production, reducing global supply. Trade Restrictions and Export Bans. India imposed an export ban in 2023 to stabilize domestic supply, leading to shortages in importing countries like Malaysia. The COVID-19 pandemic also disrupted international trade, limiting onion exports.